2001
DOI: 10.1055/s-2001-11017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the sodium/iodide symporter by retinoids - a review

Abstract: Decrease or loss of iodide uptake, due to impaired expression and/or function of the sodium/iodide-symporter (NIS), is a major obstacle to the treatment of advanced thyroid carcinomas by radioiodide therapy. Several approaches are being evaluated to optimise or restore sufficient iodide transport in those cases, among them retinoid therapy. Retinoids with their growth-inhibiting and differentiation-inducing properties have been repeatedly used for treatment and chemoprevention of various cancers. In thyroid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…It is well documented that RA stimulates thyroid iodide uptake in human thyroid follicular carcinoma cells (Schmutzler 2001), thyroid cancer (Coelho et al 2004), and thyroid gland of female rats (Silva et al 2009). We now demonstrate that although 28 days of treatment with 13-cis-RA stimulates radioiodide uptake, in fact, 14 days Table 1 Effect of all-trans-retinoic acid (RA) and 13-cis-RA for 14 days in the dose of 100 mg/kg body weight (b.w.)…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that RA stimulates thyroid iodide uptake in human thyroid follicular carcinoma cells (Schmutzler 2001), thyroid cancer (Coelho et al 2004), and thyroid gland of female rats (Silva et al 2009). We now demonstrate that although 28 days of treatment with 13-cis-RA stimulates radioiodide uptake, in fact, 14 days Table 1 Effect of all-trans-retinoic acid (RA) and 13-cis-RA for 14 days in the dose of 100 mg/kg body weight (b.w.)…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report an almost total efflux of iodine from the cells, occurring less than 1 hour after the NIS-related uptake (13)(14)(15)(16). Efflux was not significantly reduced by enzymatic or pharmacological means (14,(17)(18)(19)(20)(21)(22). Interestingly, two studies have demonstrated a long retention time for 123 I and significant tumor reduction after the application of a high dose of 131 I in NIS-transduced mice (23,24).…”
Section: Radioiodine (mentioning
confidence: 99%
“…Retinoic acid (RA) increases iodide uptake in some differentiated thyroid cancers (33,34). Moreover, in MCF-7 breast cancer cells, all-trans RA (tRA) stimulates iodide uptake after RA receptor (RAR)-induced up-regulation of the NIS gene (17).…”
mentioning
confidence: 99%